2008
DOI: 10.1097/sla.0b013e31818a15b5
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive Surgery and Perioperative Intraperitoneal Chemotherapy for Isolated Colorectal Peritoneal Carcinomatosis: Experimental Therapy or Standard of Care?

Abstract: Background-Minimally invasive coronary artery bypass grafting (miniCABG) decreases inhospital morbidity versus traditional sternotomy CABG. We performed a prospective cohort study (NCT00481806) to assess the impact of miniCABG on costs and metrics that influence quality of life after hospital discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(117 citation statements)
references
References 60 publications
2
112
1
2
Order By: Relevance
“…After exclusion of duplicated studies and 546 irrelevant articles based on abstracts and titles, 126 studies remained for full-text evaluation. Of these, 44 studies met the inclusion criteria, including nine studies in the TECAB off-pump group (10)(11)(12)(13)(14)(15)(16)(17)(18); two studies in the TECAB on-pump group (19,20); and 16 studies in the robotic MIDCAB group (10,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). One study provided separate data for both the TECAB offpump and robotic MIDCAB groups, and was included for analysis in both groups (10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After exclusion of duplicated studies and 546 irrelevant articles based on abstracts and titles, 126 studies remained for full-text evaluation. Of these, 44 studies met the inclusion criteria, including nine studies in the TECAB off-pump group (10)(11)(12)(13)(14)(15)(16)(17)(18); two studies in the TECAB on-pump group (19,20); and 16 studies in the robotic MIDCAB group (10,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). One study provided separate data for both the TECAB offpump and robotic MIDCAB groups, and was included for analysis in both groups (10).…”
Section: Resultsmentioning
confidence: 99%
“…However, this duration was measured from the time of LIMA occlusion, and included the period of time spent on target vessel identification and preparation prior to anastomosis. Similarly, although Srivastava, Poston and Subramanian reported mean total operative times of 311, 348 and 444 minutes, respectively, they also averaged 1.9-2.2 grafts, accounting for the increased operative time spent on conduit harvesting and performing the additional anastomoses (29,30,32). In addition, studies of on-pump TECAB, such as the multiinstitutional study by Argenziano and colleagues, reported longer operative times due to the need for peripheral cannulation and use of a cardiopulmonary circuit (20).…”
Section: Discussionmentioning
confidence: 99%
“…HCR was compared to multi-arterial grafting in a retrospective review, where less blood transfusion and a shorter length of stay were noted; 30-day MACCE were similar (17). Other studies have shown faster recovery after surgery (18), with quicker return to work (19) and improved quality of life scores at 3 months (20).…”
Section: Short-term Outcomesmentioning
confidence: 99%
“…The outcomes published for robotically assisted minimally invasive direct CABG approaches (Table 2) show no perioperative mortality and low complication rates. [12][13][14][15][16][17] …”
Section: Robotically Assisted Coronary Artery Bypass Grafting Throughmentioning
confidence: 99%